THE IMPLEMENTATION OF INTERACTIVE READ ALOUD IN TEACHING ENGLISH TO EFL YOUNG LEARNERS (A Case Study Conducted in a Private Elementary School in Bandung) - Hani Maruta Saarah (Journal of English and Education, 2017)
This study aims to investigate the ways classroom interactions in Interactive Read Aloud construct students’ reading comprehension, and the strategies implemented by teacher before Interactive Read Aloud to produce classroom interactions in English as a foreign language context. This study employed a case study approach, and used two types of instruments which were classroom observation, and written documents to answer the research questions. The result of the study revealed that to construct students’ reading comprehension, confirming, modeling, extending, and building interactions were produced during Interactive Read Aloud, and also revealed several strategies that were applied before Interactive Read Aloud to produce classroom interactions which were reading the book several times, formulating the learning objectives and questions, building students’ background knowledge, identifying where students prediction should be shared, and devising opportunities for students to explore the story more. It is thus recommended for EFL young learners’ teachers who implement this method to produce the interactions, and conduct the strategies before the implementation thus the interactions that construct students’ reading comprehension are produced.